Dual inhibition of IL-17A and IL-17F in psoriatic disease - Helena Iznardo; Lluís Puig (SAGE Publishing, 2021)
Psoriasis and psoriatic arthritis are chronic immune-mediated disorders with involvement of interleukin (IL)-17 cytokines in their pathogenesis. IL-17A has been considered to be the most biologically active, but IL-17F is also over-expressed in skin and synovial tissues of patients with these diseases. Many therapeutic advances have been made in the past years, but some needs remain unmet. Dual inhibitor and bispecific antibodies simultaneously targeting IL-17A and IL-17F could provide better disease control. Herein we review current evidence on bimekizumab and sonelokimab. The antigen-binding site of bimekizumab neutralizes both IL-17A and IL-17F; phase I, II, and III studies have demonstrated its efficacy and safety in psoriasis and psoriatic arthritis. Sonelokimab is a trivalent nanobody targeting IL-17A and IL-17F; phase I and II studies with this molecule have yielded promising results in psoriasis.